2016
DOI: 10.1111/vco.12229
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of lymph node metastasis identified following bilateral mandibular and medial retropharyngeal lymphadenectomy in 31 dogs with malignancies of the head

Abstract: Variable pathways of lymphatic drainage have been described in the dog head and neck. The aim of this study was to retrospectively assess the patterns of lymph node metastasis in dogs with malignancies of the head following bilateral mandibular and medial retropharyngeal lymphadenectomy. Thirty-one dogs were included. Median age at surgery was 10 years (range: 5 months to 14 years) and mean bodyweight was 21.4 ± 11.9 kg. Lymph node metastasis occurred in 14 dogs (45%), with spread to mandibular lymph nodes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
82
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 38 publications
8
82
1
Order By: Relevance
“…Such results could also be significant from a therapeutic aspect, in particular, when surgical excision or irradiation of the metastatic lymph node(s) are part of the treatment plan. In our study, most of the tumors where several metastatic LNs were investigated were located in the head and involved mandibular LNs, or were anal sac adenocarcinomas and involved the sublumbar LNs, which is consistent with other studies . Notably, we report the occurrence of bilateral prescapular LN involvement in 3 tumors (2 MCTs on the midline neck and 1 thyroid carcinoma) and bilateral inguinal LN involvement in 1 scrotal MCT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such results could also be significant from a therapeutic aspect, in particular, when surgical excision or irradiation of the metastatic lymph node(s) are part of the treatment plan. In our study, most of the tumors where several metastatic LNs were investigated were located in the head and involved mandibular LNs, or were anal sac adenocarcinomas and involved the sublumbar LNs, which is consistent with other studies . Notably, we report the occurrence of bilateral prescapular LN involvement in 3 tumors (2 MCTs on the midline neck and 1 thyroid carcinoma) and bilateral inguinal LN involvement in 1 scrotal MCT.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, we report the occurrence of bilateral prescapular LN involvement in 3 tumors (2 MCTs on the midline neck and 1 thyroid carcinoma) and bilateral inguinal LN involvement in 1 scrotal MCT. As systematic bilateral assessment of regional LNs has been recommended for head‐based tumors, the bilateral nodal assessment for other locations could be of value, although this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Which LN should be removed is currently based on its anatomical proximity to the tumour rather than on the assessment of the lymphatic drainage pathway with sentinel LN mapping methods. A recent study considering different malignancies on the head (including 3 cMCTs) found a high frequency of medial retropharyngeal LN metastasis with contralateral dissemination . In the study of Worley, 8 out 19 dogs with MCTs had a sentinel LN recognized by lymphoscintigraphy that differed from the anatomically identified RLN .…”
Section: Discussionmentioning
confidence: 99%
“…Invasive techniques such as elective neck dissection or sentinel node biopsy with subsequent histopathology and step sectioning remain the standard of care for humans . Both elective dissection and sentinel lymph node techniques have been reported in dogs; however, their therapeutic and diagnostic value have not been directly assessed . Until other techniques are validated as sufficiently sensitive alternatives, lymph node excision and histopathology (whether sentinel or regional) remains the standard of care for lymph node staging in dogs, not least due its ability to identify small metastatic aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…While fine needle aspirates may allow identification of metastasis, both false positives and false negatives are reported, and not all lymph nodes may be accessible for aspiration . Furthermore, lymphatic flow in the head and neck is complex and bilateral metastasis is possible, potentially complicating staging …”
Section: Introductionmentioning
confidence: 99%